Head Injury without Head Blow? A Rare Case of Subdural Hematoma Associated with Minute Arachnoid Cyst in a Teenage Skater - Szczygielski, Jacek; München, Dorothea; Ketter, Ralf; Ràkàsz, Lukas; Schulz-Schaeffer, Walter; Oertel, Joachim (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Skateboarding has been reported to cause diverse kinds of injuries, including head trauma. However, the risk of brain injury without direct blow to the head seems to be underestimated. In particular, the impact of the inertial forces related to the vigorous character of skateboarding tricks is not sufficiently recognized.Case Description In our report, we demonstrate a case of chronic subdural hematoma developing without previous blow to the head in a 17-year-old skater bearing small frontal convexity arachnoid cyst.Conclusion Based on the described case, the possibility of acceleration and angular forces related to skate park leisure activities resulting in subdural hematoma needs to be discussed. This risk should be critically appraised in patients carrying arachnoid cyst as a malformation predisposing to develop subdural bleeding.
Keywords: arachnoid cyst; chronic subdural hematoma; skateboard